Effects of seasonal variations of the physio-chemical properties of municipal solid waste on effective materials and resources recovery - Agwe, Tobby Michael; Twesigye-omwe, Moses N.; Ukundimana, Zubeda; Rotimi, Davies; Gupta, Sneha (Scientific reports, 2025)
Municipal solid waste (MSW) generation rate is on the rise as it is estimated to reach 3,539 million tonnes by 2050 from the 1,999 million tonnes in 2015. The seasonal variations of the physio-chemical properties of the MSW among others exacerbates its management challenges. This study aimed to conduct in-depth investigations on the seasonal variations of physio-chemical properties of the MSW generated in Kabale Municipality, southwestern Uganda to inform sustainable MSW management systems. This study revealed that this MSW is majorly plastics, with concentrations of 21.45% and 26.94% in the dry and wet seasons, respectively, which presents a more recycling potential for these plastics in the wet season. The biodegradable MSW fraction (food, paper, cardboard and garden trimming wastes), which were 35.6% and 35.34% for the dry and wet seasons, respectively, supports energy recovery from the waste in the form of biogas, with a higher potential in the wet season as supported by its higher volatile solid content for the same of 48.92% as compared to that of the dry season of 34.92%. Based on these findings, it is recommended among others that the masses be sensitized on how to generate biogas from the biodegradable fraction of this MSW.